Post-transcriptional regulations of cancer stem cell homeostasis. Issue 2 (March 2019) - Berabez, Nabila; Durand, Sébastien; Gabut, Mathieu
Abstract : Purpose of review: Although extensively studied for over a decade, gene expression programs established at the epigenetic and/or transcriptional levels do not fully characterize cancer stem cells (CSC). This review will highlight the latest advances regarding the functional relevance of different key post-transcriptional regulations and how they are coordinated to control CSC homeostasis. Recent findings: In the past 2 years, several groups have identified master post-transcriptional regulators of CSC genetic programs, including RNA modifications, RNA-binding proteins, microRNAs and long noncoding RNAs. Of particular interest, these studies reveal that different post-transcriptional mechanisms are coordinated to control key signalling pathways and transcription factors to either support or suppress CSC homeostasis. Summary: Deciphering molecular mechanisms coordinating plasticity, survival and tumourigenic capacities of CSCs in adult and paediatric cancers is essential to design new antitumour therapies. An entire field of research focusing on post-transcriptional gene expression regulation is currently emerging and will significantly improve our understanding of the complexity of the molecular circuitries driving CSC behaviours and of druggable CSC weaknesses.